The original claim related to nationality Comparative Study in Legislations (Syria, Morocco, Tunisia) Egypt, Jordan. (Damascus University Journal for legal sciences, 2025)
Comparative Arab legislation related to nationality differs in its position on granting the individual the right to file an original lawsuit whose subject is proving the individual’s enjoyment or lack of nationality, or as it is called (the original lawsuit devoid of nationality). The Syrian, Egyptian, and Jordanian legislators did not adopt an explicit position on this lawsuit and left the issue to the jurisprudence that Granting individuals this right, albeit in light of a jurisprudential difference over the legality of this lawsuit in the absence of an explicit text, while we find that the Maghreb legislation was clearer and bolder when it explicitly granted the individual the right to file this lawsuit directly without this being linked to any other payment. Or appeal a decision issued by any of the government agencies, and at the same time grant the administration, represented by the Public Prosecution, the right to file this lawsuit, equal in status between the individual and the administration. This approach, originally derived from French legislation, was more accurate and effective than Syrian law.
Keywords: Nationality; The Original Claim Related To Nationality; Syrian Law; Maghreb Legislation